O SISTEMA PRECEDENTALISTA ATRELADO AO DIREITO BRASILEIRO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work aims to analyze the precedent institute, which has its essence linked to the common law, however, mainly with the advent of the Civil Procedure Code of 2015, such institute has been increasingly discussed in homeland law, analyzed and studied in academies and doctrines, as well as having their applicability surviving.Thus, the analysis of the application of an institute that has its origins in common law in civil law is necessary, since the traditions, cultures, peoples, ethnicities and customs differ in their entirety. The method used is the hypothetical-deductive and as methodological procedures were performed doctrinal and jurisprudence analyzes.